PERLINDUNGAN HUKUM HAK PETANI TERKAIT PEMANFAATAN SUMBERDAYA GENETIK TANAMAN PANGAN DI INDONESIA - Yuliati, Yuliati (Jurnal Magister Hukum Perspektif, 2025)
Plant Genetic Resources for Food and Agriculture (PGRFA) play a crucial role in human welfare and global economic growth. However, the implementation of Intellectual Property Rights (IPR) in the agricultural sector introduces significant complexities, encompassing issues of food security, genetic engineering, genetic resource management, respect for traditional knowledge, and protection of farmers' rights and local varieties through patents or sui generis systems. This normative legal research aims to examine: (1) The legal basis for protecting Farmers' Rights related to PGRFA utilization in Indonesia; (2) The adequacy of existing IPR regulations and related laws in safeguarding these Farmers' Rights. Employing conceptual and statutory approaches, this study analyzes the prevailing legal framework. Findings reveal: (1) As a WTO member and primary PGRFA provider, Indonesia holds a strategically vital position for global food security. Yet, the government has not provided adequate legal recognition and protection for Farmers' Rights in utilizing genetic resources; (2) Indonesia's WTO membership—particularly through amendments to the Patent Law and Plant Variety Protection Law (PVPL)—has yielded detrimental impacts. The PVPL is considered inadequate in accommodating farmers' interests due to its lack of substantive clarity regarding Farmers' Rights. This research recommends a comprehensive review and amendment of the PVPL to adopt a more pro-farmer stance, strengthening recognition of customary law and considering responses from other developing WTO member nations facing similar challenges. This legal reform is imperative to balance compliance with international commitments while protecting national interests and farmers' rights. Keywords: Intellectual Property Rights, Farmers' Rights, Legal Protection